(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
An isolated prerosaur sternum is described. It has been collected in the Zorzino Limestone (Norian, Late Triassic), at the locality of Endenna (Bergamo Prealps, Lombardy, Northern ltaly). The shape and size of the bone are very similar to those of the sternum preserved in the holotype of Eudimorphodon ranzii Zambelli, 1973, collected from the same formation at the locality of Cene (Imagna valley, Lombardy, Northern Italy), and it is ascribed to this species. It represents the second well preserved Eudimorphodon sternum so far collected.